A last goodbye - Kelsey, Elin (Owlkids Books, 2020)
"This book explores the death of a loved one through the parallel experiences of other species of animals, similar to Elin's treatment of nature in You Are Stardust and problem-solving in Wild Ideas. As with Elin's previous picture books, A Last Goodbye will combine simple, poetic text with a "big idea"--in this case, the idea that death is a natural part of our lives and that many species experience sadness and mourning when their loved ones are sick and dying. From elephants to killer whales, parrots to bonobos, lemurs to humans, many animals have rituals to commemorate their loved ones and to help them through difficult times. This book broaches a difficult and scary topic through a gentle and heartfelt exploration of the natural stages of life and loss. In a parallel way to how we will be remembered by our loved ones, the book goes on to explore the ways our bodies might be remembered by the earth, repurposed to continue replenishing new life."--